Impact Assessment of Tobacco Cultivation on Soil Ecosystem Using Multi-Evaluation Techniques - Roy, Anupam; Mostafa, M.G. (CV. Science Tech Group, 2024)
Healthy soil is the key component for growing high-quality crops and sustaining agriculture. The study was carried out to evaluate the impacts of tobacco cultivation on the soil ecosystem using soil fertility, quality, and health indices. Twenty-four (24) soil samples were collected and analyzed for important soil inherent properties, as well as soil macro- and micronutrients. The results revealed that tobacco cultivation significantly reduced soil organic matter (SOM), carbon-nitrogen ratio (C: N), total nitrogen (TN), exchangeable potassium (EK), and available copper (ACu). Soil fertility index (SFI) suggested that the decline rate of soil fertility in the tobacco field (TF) (5.84%) was lower than in the non-tobacco field (NTF) (16.33%). However, the degradation rate of soil quality index (SQI) and soil chemical health index (SHI) in TF (19.23% and 27.87%) was higher than in NTF (9.98% and 14.08%). The SHI values had a positive linear relationship (0.760) with tobacco productivity. For every degree (0.01) increase in SHI value, tobacco leaf production increased by 6.40 kg/ha, while the contribution of SHI to productivity was 57.81%. Excessive application of chemical fertilizers in TF may sustain short-term soil fertility but gradually degrade soil quality and health, disrupting the long-term productivity of the soil ecosystem.